Integrate health into decision-making to foster climate action. (8th April 2021) - Vandyck, Toon; Rauner, Sebastian; Sampedro, Jon; Lanzi, Elisa; Reis, Lara Aleluia; Springmann, Marco; Dingenen, Rita Van
Abstract: The COVID-19 pandemic reveals that societies place a high value on healthy lives. Leveraging this momentum to establish a more central role for human health in the policy process will provide further impetus to a sustainable transformation of energy and food systems.